2002
DOI: 10.1093/emboj/cdf503
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule investigation of the interference between kinesin, tau and MAP2c

Abstract: Motor proteins and microtubule-associated proteins (MAPs) play important roles in cellular transport, regulation of shape and polarity of cells. While motor proteins generate motility, MAPs are thought to stabilize the microtubule tracks. However, the proteins also interfere with each other, such that MAPs are able to inhibit transport of vesicles and organelles in cells. In order to investigate the mechanism of MAP±motor interference in molecular detail, we have studied single kinesin molecules by total inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
227
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(251 citation statements)
references
References 48 publications
(70 reference statements)
20
227
3
1
Order By: Relevance
“…The interaction of dyneins with tau proteins are similar to those reported for kinesin: Run lengths are decreased at high concentrations of tau on the MT [336]. In contrast to kinesin, dynein does not detach at encounters of tau but tends to reverse direction, maybe by switching to the diffusive state of motion described above [97].…”
Section: Modification Of Mts By Maps : the Example Of Tau Proteinssupporting
confidence: 70%
See 2 more Smart Citations
“…The interaction of dyneins with tau proteins are similar to those reported for kinesin: Run lengths are decreased at high concentrations of tau on the MT [336]. In contrast to kinesin, dynein does not detach at encounters of tau but tends to reverse direction, maybe by switching to the diffusive state of motion described above [97].…”
Section: Modification Of Mts By Maps : the Example Of Tau Proteinssupporting
confidence: 70%
“…In fact, it has been shown in vitro that kinesin's attachment to the MT is hindered by tau, whereas kinesin is not affected in its motion along the filament once it is bound, i.e., processivity and walking speeds are unaffected [336,365,396]. On the other hand, another study found that kinesin had a higher probability of detachment when encountering tau patches on the MT [97].…”
Section: Modification Of Mts By Maps : the Example Of Tau Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…207,213,214 Four-repeat tau binds microtubules with a higher affinity than three-repeat tau, and an isoform imbalance in favor of four-repeat isoforms might impair kinesin-dependent anterograde traffic, because tau and kinesins bind to the microtubule surface in a competitive fashion. 28,30,146 Shifting the tau isoform ratio from fourrepeat to three-repeat isoforms by alternative splicing was therefore proposed as a therapeutic option in tauopathies. Promising results have already been achieved, with antisense oligonucleotides directed against the splice junction of exon 10 in PC12 cells leading to reduced exon 10 splicing.…”
Section: Isoform Approachesmentioning
confidence: 99%
“…Another possible role for tau is the regulation of kinesin-based transport (Ebneth et al 1998;Sparacino et al 2014;Terwel et al 2002). Tau reduces the attachment of kinesins to MTs and interferes with their transport when is overexpressed, in both in vivo and in vitro experiments (Dixit et al 2008;Ebneth et al 1998;Seitz et al 2002;Stamer et al 2002;Trinczek et al 1999;Vershinin et al 2007).…”
Section: Tau/mapt Family Of Microtubule-associated Proteinsmentioning
confidence: 99%